BRAIDED ENVIRONMENTS: A CALL TO EXPLORE RHETORIC AND MATERIALITY THROUGH AUGMENTATIVE TECHNOLOGIES. - SMITH, Steven (Metacritic Journal for Comparative Studies & Theory, 2018)
This research proposes that augmented reality technologies have the capabilities of intertwining natural spaces, material spaces, and networked (or immaterial) spaces together through the author's original idea of the between, which can in turn be used to further explore rhetorical discourse and im/materiality and bolster emerging discourse within the digital humanities. By using a variety of contemporary research on diverse topics within augmented reality and the humanities, such as the inside/outside model and the regenerative/transformative concept (each proposed by Victoria Gallagher in her works on visual rhetoric), as well as an examination of current augmented reality applications (Wikitude and Pokémon Go), the author argues that emerging applications in AR can offer scholars a variety of possibilities to explore new media and the humanities, as well as more interdisciplinary fields such as public spaces, natural spaces, digital spaces, rhetoric, science, technology, and critical cultural theory.